Moderation in Australia-Policy and Achievements - STOCKLEY,CREINA (Sociedad de Biología de Chile, 2004)
Alcohol has been consumed in Australia since European settlement in 1788. In 1998, approximately 60 % of Australians consumed an alcoholic beverage at least once per week. The effects of alcohol on the human body are dose dependent, where the harmful effects of alcohol are generally observed only when alcohol consumption exceeds moderate consumption levels of 30 to 40 g of alcohol per day. The discovery that a J-shaped curve described the relationship between level of alcohol consumption and risk of cardiovascular disease was, however, only made in 1990_cardiovascular disease is the leading cause of death in the western world. Thus prior to 1990, Australian public health policy focused primarily on the harmful effects of alcohol consumption and the health benefits of a moderate level of alcohol consumption have only recently been recognized in public policy. This paper chronicles changes in Australian Federal government policy on alcohol since the initial draft National health policy on alcohol in Australia was presented to the Ministerial Council on Drug Strategy in 1987 to the National Drug Strategic plan for action 2001 to 2003-2004 which was launched in July last year